2017
DOI: 10.1021/acssynbio.7b00019
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Recombinant Protein Expression in Escherichia coli by Manipulating Transcription, Translation Initiation Rates, and Incorporation of Noncanonical Amino Acids

Abstract: Protein synthesis in cells has been thoroughly investigated and characterized over the past 60 years. However, some fundamental issues remain unresolved, including the reasons for genetic code redundancy and codon bias. In this study, we changed the kinetics of the Eschrichia coli transcription and translation processes by mutating the promoter and ribosome binding domains and by using genetic code expansion. The results expose a counterintuitive phenomenon, whereby an increase in the initiation rates of trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
(68 reference statements)
1
25
0
Order By: Relevance
“…However, it is important to discuss two sources of this variability, which could be a common impediment in the employment of this system. First, the context and location of the site chosen for mutated to facilitate Uaa incorporation have a significant effect on the efficiency of the system [39,40], but notably, from our experience, the context, and locations could be different between in-vivo and cell-free systems [data not shown]. This subject warrants a systematic investigation that is outside the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to discuss two sources of this variability, which could be a common impediment in the employment of this system. First, the context and location of the site chosen for mutated to facilitate Uaa incorporation have a significant effect on the efficiency of the system [39,40], but notably, from our experience, the context, and locations could be different between in-vivo and cell-free systems [data not shown]. This subject warrants a systematic investigation that is outside the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Most likely, a combination of all these factors is responsible for the impaired functionality of membrane proteins when overexpressed from high levels of transcription. The fine-tuning of transcription, mRNA stability and translation is often required for optimal protein synthesis 73,75,76 . Although our study only focused here on two membrane proteins, our data suggested that the Lemo21(DE3) strain did not overexpress well at 25 °C, as compared to the C41(DE3) strain.…”
Section: Discussionmentioning
confidence: 99%
“…The functioning of TEF2 down-regulation in particular may be associated with the proteome mass reallocation from translation elongation factors (∼0.81%, SI Appendix, Fig. S22) and/or coordinated translation initiation and elongation vital for efficient protein translation (39)(40)(41). Down-regulation of the essential gene CDC39 involved in the cell cycle, conditional mutation of which resulted in G1 arrest (42), also enhanced the protein yield, confirming the universal applications of sustaining G0/G1 phase (43) and attenuating cell growth for improved protein production (44).…”
Section: Discussionmentioning
confidence: 99%